The Impact of Service Quality towards Public Satisfaction in Government Schools - Selvarajan, P. (Royal Asiatic Society and Open University of Sri Lanka, 2010)
The paper attempts to identify the public satisfaction level and the quality of services rendered by the government schools. In Sri Lanka the government schools have been functioning as monopolies in many areas and parents have the only option to send their children to government schools. It is very much essential to assess the public satisfaction of government schools. For this purpose the author has selected two national schools and two 1AB schools in Vavuniya South Zonal Educational Office. In order to understand the service quality, three variables such as fulfillment of the stakeholders’ need, quick delivery of the services and the staff’s job satisfaction are considered together as one dimension, the relationship with the public, commitment of teachers and other factors have been taken as the other dimensions for evaluation. Two different comprehensive questionnaires were utilized in the field survey to gather information and perception of public (parents and students) and the schools. (Teachers) in 2009 during the war period, many schools in Vavuniya district had been displaced to accommodate the IDPs from Wanni region. The teaching and learning activities of these schools were very much affected and they faced a vital problems of coaching the grade 5, O/L and A/L students for their competitive examinations. The findings show though these schools had been displaced in several locations and functioned with limited days with many constraints their performance; service delivery and quality have not decreased. In contrast, their service quality towards public satisfaction has been in a considerably good position.
Keywords: Service quality; Public satisfaction; Displacement; Commitment; Service delivery